Adaptation set of factors for assessing the commercial potential of technologies in different technology manufacturing branches - Zemlickienė, Vaida (Business, Management and Economics Engineering, 2018)
In the course of previous research, it has been revealed, that specifics of different technology manufacturing branches are important for assessing the commercial potential. Several technology manufacturing branches already had big input from past and now cover the most promising part of the national economy. For these reasons, it was decided to customize the model for assessing the commercial potential to biotechnology, mechatronics, laser technology, information technology, nanoelectronics. Development of a set of factors for assessing commercial potential for different technology manufacturing branches is the first stage of the model’s customization process and the main purpose of this article. The next steps will include an expert study aimed at clarifying a set of factors based on the literature analysis, identifying the significance and the meanings of factor values. The literature of technology management did not take into account the specifics of the different technology manufacturing branches, therefore sources analysing the problems of intellectual property law, problems of different engineering sciences was used. With the help of the aforementioned literature in order to adapt the set of factors to each technology manufacturing branch aims to identify the challenges and problems are faced by representatives of different technology manufacturing branches in the process commercialization.